Seeing, feeling, touching: processes of musicalization for deaf children (Orfeu, 2017)
This article seeks to find evidence to show how musical learning of deaf children takes place in an inclusive learning environment, with a view to share educational principles which  set out guidelines for teaching practices of musicalization. While laying emphasis on action research, an attempt has been made to provide significant musical learning for both deaf and normal-hearing students in the same educational environment, by adapting the necessary materials and pedagogical resources. Putting these practices into effect required finding authors who took into account the different kinds of cognitive processes suitable for deaf students or, in other words, musical activities carried out with an emphasis on the senses of seeing, hearing/feeling and touching. These senses involve acoustic, vibratory, tactile, emotional and social stimuli. In adapting the musical activities, alternative measures are employed to foster a growth in musical awareness among the students with hearing impairment. The data analysis showed that these practices have led to a wider discussion on the musical learning of deaf children. At the same time, the research defined some parameters of inclusive action which can guide the direction of planned degree courses in music and continuous teacher-training, such as those recommended in the standardized regulations for training and policymaking in Brazil. It is the responsibility of educational institutions to take measures in advance that can lead to the qualification of teachers involved in areas of musical education and in preparing instructive material that is suitable for general humanist training as a whole, while catering to  the needs of special education.
Keywords: Musical education; Deaf children; Inclusion